Konstitusionalitas Pengelolaan Migas dalam Mewujudkan Kedaulatan Energi Indonesia - Fatma Ulfatun Najicha (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
This study aims to explain and analyze constitutional oil and gas governance in the context of creating the welfare of the Indonesian people. This research is a normative study, using secondary data in the form of primary, secondary and tertiary legal materials. The results of the study found that the constitutionality of Indonesian oil and gas management is regulated and contained in the oil and gas laws and regulations which give Pertamina a dual function as operator and regulator, while the policy function is carried out by the government. This management violates the constitution and the principle of state control or state sovereignty over oil and gas as stipulated in the 1945 Constitution which is then spelled out in statutory regulations in the oil and gas sector. Another finding is that the management of oil and gas in Indonesia is still unable to have a positive impact on the Indonesian people and is detrimental to state finances. The current management is very dominated by foreign parties because the Indonesian oil and gas sector is controlled by foreign companies up to 89 percent or the potential for state financial losses due to the imposition of "cost recovery" in the oil and gas sector that is not exactly Rp 345,996 trillion rupiah per year or 1.7 billion per day.